Synthesis and Characterization of Novel Antilipidemic Agents - Chandra Sekhar, B.V.V.N.; Kumar, N. Ramesh; Mukkanti, K.; Kalyan Chakravarthy, A. (Asian Journal of Chemistry, 2011)
Different novel compounds under statin family were synthesized by introduction of more hydrophilic scaffolds in to the statin skeleton by linking the pharmacophore dihydroxy heptanoic acid moiety with more hydrophilic scaffolds to result in compounds, which may be useful as better antilipidemic agents especially as 3-hydroxy-3-methyl glutaryl coenzyme A reductase inhibitors and may improve the level of hepato selectivity and expected to reduce the risk of adverse effects. The target compounds were synthesized starting from tert-butyl-2-((4R,6R)-6- (2-aminoethyl)-2,2-dimethyl-1,3-dioxan-4-yl)acetate, a key intermediate of atorvastatin.